Gelation and luminescence of lanthanide hydrogels formed with deuterium oxide. Issue 4 (15th January 2019) - Zama, Yusuke; Yanai, Kazushige; Takeshita, Juri; Ishii, Ayumi; Yamanaka, Masamichi; Hasegawa, Miki
Abstract : Luminescent lanthanide hydrogels using the low-molecular weight gelator1 in D2 O were developed and evaluated quantitatively. Abstract : Gel formations and efficient lanthanide luminescence appeared in deuterium oxide (D2 O) medium instead of light water (H2 O), and their solvation possibilities by using luminescence lifetimes were discussed. The lanthanide ions in the hydrogel of1 obtained by H2 O (abbreviated as H2 O-Ln1 ; Ln = Eu, Tb, and Gd) in our previous report act as the coupling part between neighbor molecules for the bundle structure. Here, D2 O also acts as a medium to form the lanthanide-hydrogel of1, and increases intensities of luminescence for Tb, because a soft crystalline state reducing resonance thermal relaxation is realized. The gel-formation and luminescence band positions of Ln1 in D2 O corresponded to those in H2 O. From the observation of luminescence lifetimes in H2 O and D2 O, the number of coordinating water molecules on Eu and Tb were estimated to be around 3 or 4 for both. The luminescence intensity of Eu1 did not increase even in D2 O, due to a blue shift of the excited triplet state of1, as compared to that in H2 O.